VA Experience in Implementing Patient-Centered Medical Home Using a Breakthrough Series Collaborative - Bidassie, Balmatee (Springer US, 2014)
BACKGROUND: Veterans Health Administration (VHA) seeks to improve the delivery of patient-centered care. A Patient-Centered Medical Home (PCMH) Model, named Patient Aligned Care Team (PACT), was implemented to transform the VHA primary care delivery process. VHA used a collaborative learning model as a key approach to disseminate PACT concepts and changes. OBJECTIVE: To describe and examine VHA’s experience disseminating PACT transformation using a Breakthrough Series Collaborative method. DESIGN: Observational study. PARTICIPANTS: Approximately 250–350 individuals from 141 teams participated in six face-to-face learning sessions across 21 months. MAIN MEASURES: 1) PACT Collaborative participant surveys; 2) Coach Assessment Scores and Plan-Do-Study-Act (PDSA) data; and 3) PACT Compass (national measures to assess PACT implementation within VA healthcare system). KEY RESULTS: A majority of the participants indicated that the PACT Collaborative was necessary to implement PACT. The number of PDSAs increased steadily during the Collaborative period; 93 % (n = 1,547) of PDSAs were successfully implemented. Teams successfully achieved over 80 % of their aims, which were highly correlated with PDSAs implemented (R(2) = 0.88). The most successful aims achieved were offering same-day appointments, increasing non-face-to-face care, and improving team communication. PACT Compass indicated an improvement after the Collaborative (p-value < .000), and providers observed differences in their care practice (p-value < 0.002). This positive impact may be due to the spread of the PACT Model through the PACT Collaborative, among other learning initiatives. CONCLUSIONS: For complex collaborative models such as PACT, more than three learning sessions may be required. As VHA continues to disseminate the PACT Model through primary care, into specialty/surgical care and beyond, the Collaborative Learning Model may continue to be an effective way to leverage a small number of faculty, coaches, and industrial engineers across an extremely large population. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-014-2773-5) contains supplementary material, which is available to authorized users.